2022
DOI: 10.1038/s41581-022-00617-5
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination in patients with kidney failure: lessons from COVID-19

Abstract: Infection is the second leading cause of death in patients with chronic kidney disease (CKD). Adequate humoral (antibody) and cellular (T cell-driven) immunity are required to minimize pathogen entry and promote pathogen clearance to enable infection control. Vaccination can generate cellular and humoral immunity against specific pathogens and is used to prevent many life-threatening infectious diseases. However, vaccination efficacy is diminished in patients with CKD. Premature ageing of the immune system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 197 publications
3
54
0
Order By: Relevance
“…The analysis of the antibody response following the first vaccination cycle in healthy and fragile subjects ( 21 , 24 26 ) indicates that factors such as age, sex, and comorbidities have shown impact on the level of spike-specific IgG levels and the rate at which they decline overtime ( 27 , 28 ). Age and comorbidities, which can induce physiological and premature immune senescence, respectively, as well as chronic systemic low-grade inflammation have been considered among the most impacting factors on immune responsiveness to vaccination ( 29 31 ). Applying a linear multivariate model to assess the impact of the age and sex as confounding factors on the antibody response in this study, no significant effect was observed (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the antibody response following the first vaccination cycle in healthy and fragile subjects ( 21 , 24 26 ) indicates that factors such as age, sex, and comorbidities have shown impact on the level of spike-specific IgG levels and the rate at which they decline overtime ( 27 , 28 ). Age and comorbidities, which can induce physiological and premature immune senescence, respectively, as well as chronic systemic low-grade inflammation have been considered among the most impacting factors on immune responsiveness to vaccination ( 29 31 ). Applying a linear multivariate model to assess the impact of the age and sex as confounding factors on the antibody response in this study, no significant effect was observed (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with CKD often have impaired immunity owing to the effects of uraemic toxicity, as well as treatment-associated immune alterations, especially in patients with kidney failure who require kidney replacement therapy (KRT) such as dialysis or kidney transplantation. These immune alterations associated with kidney disease and KRT include chronic inflammation and premature immune ageing, and patients with advanced CKD are more susceptible to infections, have a diminished response to vaccination and display profound innate immune system alteration compared with the general population 44 . Below, we discuss the molecular regulation of trained immunity in the context of pathological conditions that involve the kidney.…”
Section: Trained Immunity and Immunopathologymentioning
confidence: 99%
“…Due to immune system alterations, patients with kidney failure are known to be at high risk for infections including severe COVID-19. Vaccination is of paramount importance in this vulnerable population for infections with effective vaccine 1 . Immune escape of SARS-CoV-2 and antibody fade led to the loss of protection against omicron VOC during the last months.…”
mentioning
confidence: 99%